The evaluation of Heathy School Program at junior high school receiving the National Adiwiyata - Rifai Nurmansah; Trie Hartiti Retnowati (Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
This study aims to evaluate the healthy school program in SMP Negeri 2 Kalasan. The healthy school program is a program issued by the Ministry of Education and Culture, focused on how schools can develop healthy, safe, child-friendly, and fun school movements. This study used the CIPP evaluation model with a qualitative approach, focusing on the context, inputs, processes, products of the healthy school program. Data were collected through observation, interviews, and documentary studies. Validity tests were obtained through the triangulation of data sources and techniques. Instrument validity used expert judgment, while data analysis used four steps of Miles and Huberman's model: data collection, data reduction, data presentation, and data conclusion. The findings show (1) in terms of context, SMP Negeri 2 Kalasan is a school designated by the government because it is considered capable and appropriate, and has become a model of adiwiyata schools in Sleman and won national adiwiyata school program competitions; (2) in terms of input, the design of a healthy school program can answer problems related to the input of students who have different healthy living habits; (3) in terms of process, the healthy school program has run well, but it is constrained by funding and revitalizing facilities and infrastructure because it only uses independent funds from the school; (4) in terms of product, the healthy school program at SMP Negeri 2 Kalasan has run following the objectives and has the right to continue the program, although there are still aspects that need to be improved.